Materializing Silence in Feminist Activism - Corey, Jessica Rose. author. aut Link
XIII, 204 p. 12 illus., 10 illus. in color.
Keywords: “In Materializing Silence in Feminist Activism, Jessica Rose Corey bridges the gap between academia and activism in an original and important way. It’s a lively and much-needed contribution to the fields of feminism, ethnography, and sociology.” - Emma L. E. Rees, Director, Institute of Gender Studies, University of Chester, UK This book examines how rhetorically effective uses of silence and materiality mediate feminist activism and discusses the implications of these dynamics for pedagogy. Specifically, the text establishes a theoretical foundation for what the author terms “psychosocial composing,” or “the metaphorical composing and revising of individual participants and society, and the contribution of written and visual texts as an input and output of the relationships between individuals and social culture.” This idea is examined through primary research on the Clothesline Project, an international event that invites people who have experienced gender violence (directly or indirectly) to decorate tee shirts that get hung on clotheslines in public places. Through looking at values and roles of silence in global cultures and the use of material arts in activist efforts, the author argues for the unique value of silence and materiality in individual and collective spaces. The manuscript includes discussion questions and sample teaching materials. Overall, making connections among composition and rhetoric, psychology, sociology, politics, women’s studies, art and design, pedagogy, and history, this book further demonstrates the potential interdisciplinary approaches to rhetoric and communication. Jessica Rose Corey is Director of Undergraduate Studies, Assistant Director of First-Year Writing, and Lecturer in Writing Studies in the Thompson Writing Program at Duke University. Her research interests include feminist rhetorics, activist literacies, rhetorics of silence, multimodal composition, and composition pedagogy.